Physical activity promotion in daily exercise therapy: the perspectives of exercise therapists in German rehabilitation settings - Wolfgang Geidl; Judith Wais; Cheyenne Fangmann; Ewnet Demisse; Klaus Pfeifer; Gorden Sudeck (BMC, 2019)
Abstract Background This study aims to explore exercise therapists' perspectives on the topic of physical activity promotion (PAP) with a focus on identifying (i) the intervention content and methodological approaches used for promoting physical activity (PA) in daily practice and (ii) the barriers and facilitators that affect PAP. Methods This qualitative study comprised the heads of exercise therapy departments (n = 58; 41% women; mean age = 45 years) from different rehabilitation clinics in Germany. Each participant took part in a semi-structured focus-group discussion on PAP in exercise therapy. The findings of the focus groups were processed and interpreted using a conventional qualitative content analysis. Results The exercise therapists demonstrated detailed didactic-methodological strategies and action orientations for PAP. The identified core topics of the content and methods of PAP were (1) conceptualization, (2) exercise and PA for enjoyment and pleasure, (3) education with practice-theory combinations, (4) media and materials for self-directed training, and (5) strategies to enhance personal responsibility and independence. The core topics for the associated barriers and facilitators were (1) structural conditions, (2) the role of exercise therapists, (3) the interdisciplinary rehabilitation team, (4) rehabilitant experiences and expectations, and (5) aftercare services. Conclusion The topic of PAP is addressed with a high level of variability; exercise therapists involved in this study identify various methods and content for the promotion of PA within their individual practices. However, they display a limited awareness of existing evidence- and theory-based concepts for the promotion of PA as well as underlying theories of behavioural change. This variability may be due to the lack of a defined common framework for promoting PA, insufficient emphasis being placed on PA promotion in the current curricula and training, or extensive conceptual differences within German exercise therapy departments (e.g. different weighting of PAP).